INTERPRETASI EKONOMI HASIL ANALISIS STATISTIK MELALUI PENDEKATAN ELASTISITAS - Masyhuri, Masyhuri (Fakultas Ekonomi, UIN Maliki Malang, 2011)
This paper aims to mendeskripasikan different interpretation of the results of the analysis ofthe value (unit) with a regression coefficient of elasticity values usingpercentage units (%). Themethod of analysis using the descriptive approach of regression analysis of the roadmap research students of the Faculty of Economics State Islamic University (UIN) MalangÂ MaulanaÂ MalikÂ Ibrahim last five years (2005-2010). The results showed, that a researcher in interpreting the processed data is veryimportant 'unit' was wearing. If the interpretation of the results of the analysis used the word 'unit', then it is quite relevant to regression analysis. However, if the estimatoruses the word 'prosentse' (%), it must use a mechanism of calculating the level of elasticity. On this basis, it is recommended to the reader or researcher the next, that the interpretation of the results though the use prosentse, the Cobb Douglas analysis is quite relevant because the coefficient has shown the level of elasticity.